Prematurity in scientific discovery : on resistance and neglect - Hook, Ernest B., 1936- (University of California Press, 2002)
For centuries, observers have noted the many obstacles to intellectual change in science. In a much-discussed paper published in Scientific American in 1972, molecular biologist Gunther Stent proposed an explicit criterion for one kind of obstacle to scientific discovery.